KESALAHAN UMUM MENGENAI KESESUAIAN HUBUNGAN SUBYEK- PREDIKAT DALAM KONTEKS KALIMAT POSITIF SIMPLE PRESENT TENSE YANG DIBUAT OLEH SISWA KELAS 3 SLTP NEGERI I GUBUG-GROBOGAN DAN TINDAKAN PREVENTIF GURU DALAM MEMINIMALKAN KESALAHAN - Arif Widagdo (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2006)
The study objectives are to determine common errors and the cause ofthe errors on the subjects• predicate concord of positive sentences in simple present tense usually made by junior high school student. Since the subject-predicate concord has many kinds of mies it may be difficult to learn. The popu• lation of this study was the J•d year junior high school student ofSLTP Negeri T Gubug Purwodadi. The sample were 60 students or 21 % of population. A test was used for instrument in form of composition of multiple choice. to measure the strength ofthe validity and reliability and a try out test was conducted. The result show that the instrument is valid and reliable. The student test resulted that the student competency was low since only 26.60° o of student mastered the subject while the 73,35% not mastered. A lots of exercises both wrirten and orally will be useful to master subject-predicate concord.